New species of Pheretima (Oligochaeta: Megascolecidae) from the Mt. Malindang Range, Mindanao Island, Philippines - Aspe, Nonillon M.; James, Samuel W. (Zootaxa, 2014)
We provide descriptions, with illustrations of internal structures, for 18 new species of Pheretima from Mt. Malindang, Misamis Occidental Province, Mindanao Island, Philippines. Among the 18 species, 11 belong to the P. sangirensis species group, characterized by having a pair of spermathecal pores in the intersegmental furrow of 7/8 and lacking penial sheaths in the copulatory bursae: P. maculodorsalis n. sp., P. tigris n. sp., P. immanis n. sp., P. lago n. sp., P. nunezae n. sp., P. boniaoi n. sp., P. malindangensis n. sp., P. misamisensis n. sp., P. wati n. sp., P. longiprostata n. sp., and P. nolani n. sp. One species, P. longigula n. sp., belongs to the P. montana species group, characterized by having a pair of spermathecal pores in the intersegmental furrow of 7/8 and penial sheaths in the copulatory bursae. Two species, P. vergrandis n. sp. and P. concepcionensis n. sp., are monothecal. Three species, P. adevai n. sp., P. lluchi n. sp., and P. potonganensis n. sp., belong to the P. darnleiensis species group, characterized by having either four or five pairs of spermathecae from vi to ix, with a fifth pair variably present in segment v. One species, P. subanensis n. sp., is athecate. All species described here from the Mt. Malindang Range are probably native rather than introduced, and probably do not represent range extensions of species known from neighboring islands in Southeast Asia. We provide an identification key to the Pheretima species from Mt. Malindang.